Once Upon a Village - Adebayo, Augustus (HEBN Publishers Plc, 1988)
Once Upon a Village is a personal but engaging account of the author's childhood life in a village in Ondo State, Nigeria. The author recounts, with relish and imaginative ability, his early life and adventures in the village and at school$1! =s
Keywords: Juvenile Fiction / Adventure